Entre o liberalismo político e o socialismo democrático : uma biografia política de João Mangabeira (1880-1964) - Herbert Gler Mendes dos Anjos (2024)
The present work aims to investigate the trajectory and political ideas of João Mangabeira (1880-1964), a jurist and politician from Bahia who, among other things, was a Federal Deputy, Senator, constitutionalist active in the Itamaraty Subcommittee, responsible for the constitutional draft of 1934, activist lawyer against the authoritarian escalation that gave rise to the Estado Novo (1937-1945), founder of the Democratic Left (ED) and the Brazilian Socialist Party (PSB), candidate for President of the Republic in the 1950 elections and Minister of State during the João Goulart Government (1961-1964). We seek to analyze the character's long public trajectory from the First Republic (1889-1930) to the civil-military coup of 1964, emphasizing his ideas and the ways in which he sought to intervene in the different situations that marked the Brazilian Republic during the first half. of the 20th century